Improving Relevance Feedback in Image Retrieval by Incorporating Unlabelled Images - Guizhi Li (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
In content-base image retrieval, relevance feedback (RF) schemes based on support vector machine (SVM) have been widely used to narrow the semantic gap between low-level visual features and high-level human perception. However, the performance of image retrieval with SVM active learning is known to be poor when the training data is insufficient. In this paper, the problem is solved by incorporating the unlabelled images into the learning process. We proposed a semi-supervised active learning algorithm which uses not only labeled training samples but also unlabeled ones to build better models. In relevance feedback, active learning algorithm is often used to reduce the cost of labeling by selecting only the most informative data. In addition, we introduced a semi-supervised approach which employed Nearest-Neighbor technique to label the unlabeled sample with a certain degree of uncertainty in its class information. Using these samples, Fuzzy support vector machine (FSVM) which takes into account the fuzzy nature of some training samples during its training is trained. We compared our method with standard active SVM on a database of 10,000 images, the experiment results show that the efficiency of SVM active learning can be improved by incorporating unlabelled images, and thus improve the overall retrieval performance. DOI: http://dx.doi.org/10.11591/telkomnika.v11i7.2807